Design issues in setting up of a highly synchronous human-in-the-loop system - Li, Yu Fei (2022)
In Human-machine interaction, information is communicated between a human and the machine via user interfaces. Consequently, the measures and level of insights that can be derived from such studies will be dependent upon the context under which the experimental setup was designed for. This paper highlights a successful highly synchronous human-in-the-loop (HITL) experimental system that can be used to measure situational awareness in Air Traffic Monitoring. The system setup consists of a NARSIM radar interface that displays the relevant aircraft information, a secondary control computer for the recording processing, and storage of the captured neurophysiological inputs, a remote eye tracker, and an electroencephalogram (EEG), the latter two of which provide the input. In setting up such a system, discussion of key design consideration on system compatibility and information transferability, spatial and resolution accuracy, data input sources and synchronization, software selection, and the ease of results validation will be made.